Trading in agricultural property in the light of the freedom of movement of capital – from the case law of the Court of Justice of the European Union - Włodarczyk, Beata (Przegląd Prawa Rolnego, 2019)
The aim of the article is to outline the legal issues of trading in agricultural property in the European Union, which is entirely subject to basic treaty rules. The free movement of capital, regulated in Article 63 of the Treaty on the Functioning of the European Union, is of particular importance in relation to cross-border operations connected with trading in agricultural property. Therefore the legislation in force and applicable in EU Member States should ensure that citizens of other Member States have the possibility of exercising this freedom. However, the free movement of capital is not absolute. In the light of the established case-law of the Court of Justice of the European Union, regulations limiting free movement of capital may be introduced at national level, provided that they pursue general interest objectives and comply with the principles of proportionality and non-discrimination.